Hak Pilih bagi Penyandang Disabilitas Mental Ditinjau dari Perspektif Hak Asasi Manusia - Tony Yuri Rahmanto (Balai Besar Litbang Pelayanan Kesejahteraan Sosial, 2019)
The political dynamics in Indonesia at the end of 2018 are again warmed up due to the issuance of the Circular Letter of the General Election Commission of the Republic of Indonesia which states that persons with mental disabilities have the right to vote so that they can be recorded as voters. This seems to lead to diverse opinions where in the end the government accommodates the rights of persons with mental disabilities but on the other hand raises concerns for people with mental disabilities whether they can exercise their right to vote properly or not. The purpose of this paper is to provide a comprehensive understanding of persons with mental disabilities, to describe the legal basis for suffrage for persons with mental disabilities and to describe the suffrage rights of persons with mental disabilities viewed from the perspective of human rights. This research is a normative legal research with a qualitative approach that aims to uncover facts and present the existence of circumstances, phenomena, and circumstances that occur based on the study of literature. In this paper describing that persons with mental disabilities actually can still be given the right to vote in general elections because so far there is no prohibition for persons with mental disabilities to obtain their rights. While from a human rights perspective, it is imperative that giving voting rights for persons with disabilities is absolute because persons with mental disabilities are also part of citizens who are given the right by the state to be able to participate in the democratic process procedurally.